Family as a Socio-economic Actor in the Political Economies of East and South East Asian Welfare Capitalisms - Papadopoulos, Theodoros; Roumpakis, Antonios (Social Policy & Administration, 2017)
In this article, we revisit Karl Polanyi's concept of 'oikos' in order to reconceptualize the role of the family as both a welfare provider and an economic actor in the social reproduction of East and South East Asian welfare capitalisms. Our article is structured in four parts. First, we critically review existing approaches on the characteristics of welfare capitalism in East and South East Asia. We argue that existing approaches tend to isolate family as a welfare provider and neglect how the role of the family is institutionalized as a collective actor. The second part focuses on the role of the family in the social reproduction of welfare capitalism, and explores how, in East and South East Asia, the specific conditions for family's role as an economic actor were institutionalized historically. The third part revisits Polanyi's concept of 'oikos' and how 'householding' constitutes one of the most important forms of economic action allowing us to examine the family as a socio-economic actor. In the fourth section, we provide an analysis of families' available strategies and discuss evidence related to private education expenditure, household debt and labour market income share. We conclude by highlighting the need to re-articulate the importance of family as a collective socio-economic actor that, despite recent reforms and path departures, remains at the epicentre of East and South East Asian welfare capitalisms.
Political Science; Public Administration
Keywords: East and South East Asia; OIKOS (The Greek word); debt; economic conditions in Asia; families & economics; family; households and economics; social reproduction; welfare capitalism; welfare state

Why TTIP is an unprecedented geopolitical game-changer, but not a Polanyian moment - Eliasson, Leif Johan; García-Duran, Patricia (Journal of European Public Policy, 2017)
This contribution argues that the Transatlantic Trade and Investment Partnership (TTIP) is unprecedented, not because it constitutes a Polanyian moment, but rather because it offers an alternative to multilateralism through the World Trade Organization (WTO). Never before has bilateralism offered such a 'best alternative to no agreement' (BATNA) to members of the core decision-making body of the WTO negotiating arm, making TTIP an unprecedented geopolitical game-changer. The anti-TTIP campaign, however, has not been driven by concerns with either geopolitics or trade liberalization, but rather fears about the European Union's (EU's) bargaining power. By strategically focusing on the potential impact on public policy and safety standards, normative arguments promulgated by opponents reflect concerns with perceived threats to the status quo and a willingness to preserve the same. The United States is presented (implicitly) as more powerful than the EU, and therefore perceived as able to impose its preferences, which are considered too neoliberal.
Political Science
Keywords: European Union; TTIP; Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); bilateralism; free trade; geopolitics; trade

Fictitious Freedom: A Polanyian Critique of the Republican Revival - Klein, Steven (American Journal of Political Science, 2017)
Prominent republican theorists invoke anonymous orders such as the market as mechanisms that secure freedom as non-domination. Drawing on Karl Polanyi's account of fictitious commodities and demonstration of the impossibility of a just and rational market society, this article critically scrutinizes neo-republican assumptions regarding the market, develops an alternate social theory within which to situate the ideal of non-domination, and illustrates the importance of this reconfiguration for the kind of collective agents and political strategies that can be expected to advance republican freedom in the economy.
Political Science
Keywords: Polanyi - political & social views; economic liberty; markets; republicanism; social theory

Re-reading Friedrich Hayek and Karl Polanyi in the Late-Modern Condition of Fragility - Cha, Taesuh (Political Studies Review, 2017)
The cardinal role of complexity in Friedrich Hayek’s theory of the market has hardly gone unnoticed. Indeed, there is now a considerable corpus of literature that has established the importance of spontaneity as a central concept around which neoliberal economic theory revolves. However, as William Connolly analyzes, its closed conception of economic processes simplifies real economic volatilities and ignores both modes of self-organization and creativity found in democracy and social movements that periodically irrupt into market processes. This article builds upon this critique of neoliberalism and employs Karl Polanyi’s genealogy of modern capitalism to understand historical imbrications between the market and the social and their contribution to the fragility of capitalism. Polanyi’s notions of “(dis-)embeddedness” and the “double movement” not only show us a more “complex” view of modern political economy but also provide us with important lessons for political responses to the recent crisis of neoliberal capitalism.
Political Science
Keywords: CONNOLLY; William; Friedrich Hayek; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; capitalism; complexity (philosophy); complexity theory; fragility; genealogy

When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Political Science
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union; 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism

The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Political Sciences; Development Studies
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

The Second Time Around? Polanyi and Today's Fascist Tendency - Sandbrook, Richard (Peace Magazine, 2017)
Discusses the relevance of Polanyi’s double movement in light of increasing support for far-right, authoritarian and neo-fascist movements in Europe and North America. The author quotes The Great Transformation on how fascism “was rooted in a market system that refused to function” (21), however, he chooses to center his analysis on an unpublished essay of Polanyi’s entitled “The Fascist Virus”. From this, he extrapolates that fascism operates like a disease within liberal capitalism, becoming lethal when tensions between capitalism and democracy hit crisis levels and unleashing itself into the body politic (20).
Peace Studies
Keywords: fascism; right-wing populism

Karl Polanyi: A Life on the Left - Kurtz, Geoffrey (New Political Science, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); book review

What American Government Does - Luger, Stan; Waddell, Brian (JHU Press, 2017)
It has become all too easy to disparage the role of the US government today. Many Americans are influenced by a simplistic anti-government ideology that is itself driven by a desire to roll back the more democratically responsive aspects of public policy. But government has improved the lives of Americans in numerous ways, from providing income, food, education, housing, and healthcare support, to ensuring cleaner air, water, and food, to providing a vast infrastructure upon which economic growth depends. In What American Government Does, Stan Luger and Brian Waddell offer a practical understanding of the scope and function of American governance. They present a historical overview of the development of US governance that is rooted in the theoretical work of Charles Tilly, Karl Polanyi, and Michael Mann. Touching on everything from taxes, welfare, and national and domestic security to the government’s regulatory, developmental, and global responsibilities, each chapter covers a main function of American government and explains how it emerged and then evolved over time. Luger and Waddell are careful to both identify the controversies related to what government does and those areas of government that should elicit concern and vigilance. Analyzing the functions of the US government in terms of both a tug-of-war and a collaboration between state and societal forces, they provide a reading of American political development that dispels the myth of a weak, minimal, non-interventionist state. What American Government Does represents a major contribution to the scholarly debate on the nature of the American state and the exercise of power in America. – Sidney Plotkin, Vassar College, coauthor of Private Interests, Public Spending: Balanced-Budget Conservatism and the Fiscal Crisis
Political Science
Keywords: American government; history - Americas (North; Central; South; West Indies); political science - history and theory

Karl Polanyi: a life on the left - Payne, Anthony (International Affairs, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; biography; book review; economists; nonfiction

Karl Polanyi, The Great Transformation and a New Political Economy - Watson, Matthew; Holmes, Christopher; Clift, Ben (brunobertez, 2017)
Karl Polanyi, The Great Transformation and a new political economy Professor Matthew Watson, Assistant Professor Christopher Holmes and Professor Ben Clift, Politics and International Studies Avert…
Political Science; International Relations
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; MARX; Karl; 1818-1883

Reviving Hayek’s Dream - Worth, Owen (Globalizations, 2017)
This short piece suggests that the roots of the successful Brexit vote can be found in the free market purity that was implicit within the ideals behind Thatcherism. Whilst the rhetoric of populist and British (or in many parts English) nationalism were utilised in order to win support, the ideological driving force implicit within many Brexit figureheads rested in the belief that the EU watered down their visions of a harder neoliberal reality. Yet, by stimulating right-wing reactionary forces, they may have created more than they bargained for. I concur with Karl Polanyi that free market liberalism tends to generate the forces of its own demise.
Political Science
Keywords: Brexit; Brexit Referendum; 2016; free enterprise; liberalism; market idealism; neoliberalism; populism; the far right

Karl Polanyi in Dialogue: A Socialist Thinker for our Times - Brie, Michael (Black Rose Books, 2017)
Featuring essays from Michael Brie (Rose Luxemburg Foundation, Berlin), Nancy Fraser (New School for Social Research, New York) and Kari Polanyi-Levitt (McGill University, Montreal). The contemporary Left fights its political battles on various fronts: protesting the crippling structural inequalities that sustain neoliberal economic policy; developing sustainable, community-based alternatives to the consumerism and short-termism that exacerbate the environmental crisis; and advocating for the cultural recognition, emancipation and celebration of the diversity and pluralism of human identity. But despite this versatility the Left appears to be in worldwide retreat whilst an aggressive new ‘Alt-Right’ is taking to the internet and the streets, regurgitating a regressive and patriarchal vision of society that has already won startling political victories in the US and Europe. Amidst the vertiginous tension of such a crisis, Michael Brie argues for an urgent theoretical and practical reorganisation of the Left. Developing the work of philosopher and social theorist Karl Polanyi, Brie advocates an alliance of socialist liberals and libertarian ‘commonists’ that unites contemporary campaigns for recognition, difference and human dignity with more traditional struggles for social welfare and economic democracy. Starting with Nancy Fraser’s critical reappraisal of Polanyi in her article “A Triple Movement? Parsing the Politics of Crisis after Polanyi” (included), Brie powerfully reinterprets Polanyi’s thought for present times, developing concrete proposals for a Polanyian political response to neoliberalism, an ascendent authoritarian right and the ongoing threat of global ecological disaster. Also included are two articles by Polanyi translated into English for the first time and Kari Polanyi-Levitt’s lecture at the Rosa Luxemburg Foundation “From the Great Transformation to the Great Financialisation”.
Philosophy; Political Science
Keywords: biography; ecology; economics; feminism; history; labor; labour; politics; racism; sociology

The moral economists: R.H. Tawney, Karl Polanyi, E. P. Thompson, and the critique of capitalism - Rogan, Tim (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism–R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."
History; Political Science
Keywords: HENRY; Richard; PALMER; Edward; TAWNEY; R.H.; THOMPSON; E.P.; capitalism; moral and ethical aspects; moral economy; socialism

Progressive Responses to Populism: A Polanyian Critique of Liberal Discourse - Yarrow, David (The Political Quarterly, 2017)
This article explores the recent rise of populist politics from the perspective of Karl Polanyi's theory of the ‘double movement’. It firstly introduces Polanyi's understanding of interwar populism, and relates this to his broader critique of liberal economic thought. This framework is then used to analyse three prominent explanations for populism which emerged in the wake of the UK's 2016 EU referendum: globalisation; cultural reaction; and social media. I show how each of these explanations exogenises contemporary populist movements, narrating them as something external to the liberal economic restructuring pursued globally since the 1980s. Failing to diagnose adequately the causes of contemporary populist movements, which lie in this utopian attempt to treat labour as a commodity, they cannot support an intellectually coherent progressive response to Brexit. Finally, I outline a political agenda centred on labour de-commodification, which could directly address populist grievances and reclaim the discourse of ‘taking back control’ for the left.
Political Science
Keywords: Brexit; commodification; double movement; labour; liberal discourse; populism